JHEA, Volume 10, n° 1, 2012 - Full Issue - journal system (Journal of Higher Education in Africa, 2012)
Contents Participatory Action Research as Platform for Community Engagement in Higher Education Godwell Nhamo ................................ 1 L’Université de Kinshasa : « colline du savoir », colline des transactions Bernard Mumpasi Lututala.............................. 23 University Expansion and the Challenges to Social Development in Kenya: Dilemmas and Pitfalls Ibrahim Ogachi Oanda & James Jowi ................................. 49 Comment l’université sénégalaise se territorialise : modalités d’une cohabitation dynamique Jean Alain Goudiaby ........................................ 73 The Dynamics of University Transformation: A Case Study in the Eastern Cape Province of South Africa Rómulo Pinheiro, Gerald Wangenge Ouma & Pundy Pillay ........................ 95 Leadership in Kenyan Public Universities and the Challenges of Autonomy and Academic Freedom: An Overview of Trends Since Independence Daniel N. Sifuna ................................... 121 The Roles of Higher Education in the Democratization of Politics in Africa: Survey Reports from HERANA Robert Mattes & Thierry M. Luescher-Mamashela ............... 139 L’Université de Ouagadougou : territoire de la contestation et de la répression des étudiants Issa Sory ............................................ 171